(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
This study aimed to understand the epistemic views of history teachers on school history as specialised subject of knowledge. This study adopted the qualitative research approach and interpretivism paradigm. I purposively sampled seven professionally qualified history teachers. For data generation, I used card sorting. What emerged was an unquestionable epistemic certainty to which the teachers steadfastly returned. Broadly speaking, to them school history as the specialised subject of knowledge was about past human actions, promoting human rights, critical thinking, and understanding values. In many ways this spoke of a fixed mindset in which the ideas of what school history should be—namely, procedural historical thinking as part of an analytical approach to the subject as found in the CAPS-History document—had limited to no impact. This could be attributed to the fact that the rural teachers who participated in this study had limited opportunities to be exposed to training related to the CAPS-History curriculum. Hence, their knowledge about school history is rooted in their historical, social, political, educational, and economic reality in which historical knowledge, common or general knowledge, political knowledge, generic skills, and character education are key matters.